Designing and Computational Analysis of Chimeric Avian Influenza Antigen: A Yeast-Displayed Universal and Cross-Protective Vaccine Candidate (Journal of Poultry Sciences and Avian Diseases, 2023)
This study describes the development of a cross-protective vaccine candidate against avian influenza virus, which was designed using M2e, a highly preserved antigen. The consensus sequence of M2e was obtained using 31 sequences of avian influenza virus subtypes (H5N8, H5N1, H9N2, and H7N9) isolated from seven avian species in five Asian countries. An adjuvant, a partial sequence of flagellin, was also considered. Two chimeric antigens were designed and virtually cloned and expressed using the PYD1 vector and EBY100 yeast strain. Molecular dynamic simulations were used to assess the stability and conformational features of these antigens. The likelihood of detection by a specific monoclonal antibody, MAb148, was estimated for the designed peptides using docking studies. The second chimeric antigen was more compact and stable than the first design, but it was less detectable by MAb148. In the first design, two of the four desired epitopes ("SLLTEVETP") were exposed, while only a partial sequence of this epitope was detectable in the second design. In contrast to the second chimeric antigen, electrostatic, and binding energies related to the interaction of the first antigen and MAb148 were significantly closer to the positive control. This suggests that epitopes of the first chimeric antigen could be correctly located in the specific paratope of MAb148. In conclusion, the first chimeric antigen exhibits favorable conformational features and epitope-paratope interactions, highlighting its potential as a promising cross-protective vaccine candidate against a range of avian influenza virus subtypes.